Physicochemical Properties and Liposomal Formulations of Hydrolysate Fractions of Four Sea Cucumbers (Holothuroidea: Echinodermata) from the Northwestern Algerian Coast - MECHETA, Asmaa; HANACHI, Amine; JEANDEL, Carole; ARAB-TAHRANY, Elmira; BIANCHI, Arnaud; VELOT, Emilie; MEZALI, Karim; LINDER, Michel (Molecules, 2020)
To promote the nutritional and pharmacological values of four sea cucumber species (Holothuria poli, H. tubulosa, H. arguinensis, and H. sanctori), harvested from the Algerian coast, we aimed to study their proximate composition, fatty acid profile and angiotensin-converting enzyme (ACE) inhibitory activity. Their phospholipids were also used to elaborate nanoliposomes and to encapsulate peptides obtained from the same source. After the physico-chemical characterization of nanoliposomes and peptides, in vitro analyses were realized. The four holothurian species showed a high amount of protein (49.26–69.34%), and an impressive lipid profile of 27 fatty acids, mainly composed of polar fatty acids (91.16–93.85%), with a high polyunsaturated fatty acids (PUFA) content (50.90–71.80%), particularly eicosapentaenoic acid (EPA) (5.07–8.76%) and docosahexaenoic acid (DHA) (4.86–7.25%). A high phospholipids amount was also found (55.20–69.85%), mainly composed of phosphatidylcholine (PC) (51.48–58.56%). Their peptide fractions exhibited a high ACE inhibitory activity (IC50 0.30 to 0.51 mg/mL). The results also showed that the nanoliposomes do not induce cytotoxicity and cell death in human MSCs and no perturbation of proliferation for all the times and the tested concentrations, as well as the combined nanoliposomes and hydrolysates (HTS) at a concentration of 0.1 mg/mL. All four sea cucumbers show potential as a new source for omega-3, omega-6, and bioactive peptides.
Keywords: sea cucumbers; PUFA; peptide; ACE; nanoliposome; phospholipids; Algerian coast